2017
DOI: 10.3892/ol.2017.6784
|View full text |Cite
|
Sign up to set email alerts
|

HLA-mediated tumor escape mechanisms that may impair immunotherapy clinical outcomes via T-cell activation

Abstract: Although the immune system provides protection from cancer by means of immunosurveillance, which serves a major function in eliminating cancer cells, it may also lead to cancer immunoediting, molding tumor immunogenicity. Cancer cells exploit several molecular mechanisms to thwart immune-mediated death by disabling cellular components of the immune system associated with tumor recognition and rejection. Human leukocyte antigen (HLA) molecules are mandatory for the immune recognition and subsequent killing of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 106 publications
1
45
0
Order By: Relevance
“…Gene features from the complete Gene expression-based models are more enriched in biological process related to immunological response such as T cell costimulation, immunoglobin response (Figure 9b). Impaired expression of HLA-DQB1 due to change in methylation pattern of gene is associated with esophageal squamous cell carcinoma by altering immune response pattern [49].…”
Section: Resultsmentioning
confidence: 99%
“…Gene features from the complete Gene expression-based models are more enriched in biological process related to immunological response such as T cell costimulation, immunoglobin response (Figure 9b). Impaired expression of HLA-DQB1 due to change in methylation pattern of gene is associated with esophageal squamous cell carcinoma by altering immune response pattern [49].…”
Section: Resultsmentioning
confidence: 99%
“…Reliable markers need yet to be established to predict responsiveness to immunotherapy and to identify the subset of patients expected to benefit the most. The most promising markers currently under study comprise microsatellite instability (MSI), high tumor mutational load (TML) (83,84), mismatch repair deficiency (dMMR) (85), HLA class-I diversity (86,87), and biomarker expression (e.g., PD1, PD-L1) (88). Screening 389 cases of CUP, Gatalica et al found that 28% of samples were positive for one or more of said predictive markers (89).…”
Section: Immunotherapymentioning
confidence: 99%
“…Different TAAs expressed by CSCs, such as ALDH1A1, CD133, CEP55, COA-1, EpCam, HEATR1 IL-13Rα2, SOX2, and DNAJB8, are recognized by T cells and are potentially capable of eliciting an effective antitumor immune response [28]. To prevent attack by immune cells, neoplastic cells in clinically detectable tumors often downregulate the expression of proteins involved in ag presentation, thus preventing the exposure of TAAs in tumor cell membranes [29]. This phenomenon appears to be enhanced in CSCs of several cancer types.…”
Section: Cscs: Leading Actors In the Intratumor Immunosuppressive Scementioning
confidence: 99%